National Identity in Mid-Nineteenth Century Birmingham. (4th May 2022) - Taylor, Samuel
ABSTRACT: Most current academic investigations of national identity by Linda Colley and Peter Mandler et al, are substantially based on the experience of London. This article focuses on how national identity was perceived and represented by four individuals in mid-nineteenth-century Birmingham. Birmingham's significance as an international manufacturing centre; a centre for campaigns for franchise reform and the abolition of slavery; and a location for migration meant that national identity was a matter of great interest. These four individuals were Joseph Sturge, a middle-class radical abolitionist; John Bright, the Liberal MP; George Edmonds, a campaigner from an artisanal background; and George Dawson, an influential preacher. The article draws out similarities and differences in their views by investigating how they saw the nation and who they thought belonged to it. The article moves beyond the London-centric historiography of national identity by assessing national identity discourses in an important provincial town.